1994
DOI: 10.1111/j.1365-2249.1994.tb06111.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune complex glomerulonephritis is induced in rats immunized with heterologous myeloperoxidase

Abstract: SUMMARY Anti‐neutrophil cytoplasmic antibodies (ANCA), including anti‐myeloperoxidase (MPO) antibodies, are associated with pauci‐immune necrotizing small vessel vasculitis or glomerulonephritis, 1n order to substantiate a pathogenic role for ANCA, an animal model of pauci‐immune ANCA‐induced glomerulonephritis or vasculitis is required. Brouwer et al. reported pauci‐immune glomerulonephritis in rats immunized with human MPO followed by perfusion of kidneys with lysosomal enzyme extract combined with H2O2, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 15 publications
0
19
1
Order By: Relevance
“…This model might explain the paucity of the immune deposits in ANCA-associated glomerulonephritis [2,16]. Other studies however suggested that this model might represent immune complex-mediated glomerulonephritis, dissimilar to human crescentic glomerulonephritis [17]. Although an immune complex-mediated process in ANCA-induced inflammation may be speculated, it may differ from classic immune complex-mediated vasculitis, which requires gross accumulation of the immune complexes and typically does not result in severe necrotizing injury [1].…”
Section: Discussionmentioning
confidence: 99%
“…This model might explain the paucity of the immune deposits in ANCA-associated glomerulonephritis [2,16]. Other studies however suggested that this model might represent immune complex-mediated glomerulonephritis, dissimilar to human crescentic glomerulonephritis [17]. Although an immune complex-mediated process in ANCA-induced inflammation may be speculated, it may differ from classic immune complex-mediated vasculitis, which requires gross accumulation of the immune complexes and typically does not result in severe necrotizing injury [1].…”
Section: Discussionmentioning
confidence: 99%
“…Most interestingly, ICX deposits were observed in the kidney shortly after perfusion, but these ICX appeared to have dissolved already at the time that renal damage was at its peak. Using a similar approach, Yang et al [24] observed that the degree of histological injury correlated with the amount of glomerular IgG immune deposits and concluded that this perfusion rat model is an example of ICX-mediated glomerulonephritis.…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%
“…Yang et al [21] recently could not reproduce the pauciimmune character of the lesions in this model, although they mentioned that some glomeruli had proliferative lesions without immune deposits. Nevertheless, they observed a correlation between the severity of the histologie lesions and the amount of IgG deposition.…”
Section: (Accepted For Publication 28 December 1994)mentioning
confidence: 92%